Application of biofield in medicine - Tay, Yak Koon. (2008)
Bioelectricity occurs in all living tissue. The origins of bioelectricity lie within cell membranes, which maintain a small potential difference between the interior and exterior of each cell. A fluctuation of this potential acts as a signaling mechanism that permits nerves to interact, muscles to contract, and communication to occur over the whole body. The writer would like to present the idea that electromagnetic fields are carriers of biological important information. A large number of diseases can also be diagnosed and sometimes treated on the basis of their electrical activity. In this study, various models and numerical solutions of biof ield problems are demonstrated. A comparison of these numerical methods is also discussed. Boundary conditions associated with the problems are shown. This study further presents the application of bioelectric field phenomena in medicine and shows its direct impact on the health and well being of humans in the coming years and decades. The writer also discusses two possible future applications of biofield in medicine to illustrate further how bioelectromagnetism presents new and important opportunities in the area of diagnostic and therapeutic use.